La vulneración del debido proceso en procedimientos administrativos sancionadores y el abuso del derecho. Estudio de Caso: Verónica Abad - Huilca Jurado, María José (2026)
This research analyzes violations of due process in administrative sanctioning procedures in Ecuador, which undermine the legitimacy of decisions and public trust. The case study of former Vice President Verónica Abad exemplifies these irregularities, revealing inadequate notification, limited defense opportunities, disproportionate sanctions, and potential political misuse of sanctioning authority. The study aims to assess these implications and recommend reforms to protect rights in such procedures. A qualitative, non-experimental design was used, combining legal and doctrinal analysis with semi-structured interviews of public officials in Riobamba. Data were processed using ATLAS.TI software. The results revealed deficiencies in the application of due process, arbitrariness in the exercise of sanctioning powers, lack of independence of authorities, and limitations in constitutional oversight, while also confirming the existence of practices that violate procedural guarantees. The conclusions highlight the need to strengthen the regulatory framework, ensure impartiality in proceedings, and promote effective defense mechanisms.